2022
DOI: 10.4178/epih.e2022038
|View full text |Cite
|
Sign up to set email alerts
|

Occupational inequalities in mortality in Korea: an analysis using nationally representative mortality follow-up data from the late 2000s and after

Abstract: Many Korean and international studies have found higher mortality rates and poorer health conditions among manual workers than among non-manual workers. However, a recent study using unlinked data argued that since the economic crisis in Korea in the late 2000s, the mortality estimates of male Korean non-manual workers have been higher than those of manual workers. Our work using individually linked data from the late 2000s and after aimed to examine mortality inequality by occupational class. We analyzed Kore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Over the 24-year period, SMR of suicide and CCVD were highest in SFF and MNG among males and females, respectively ( Appendix A ). Appendix B displays the result of analyzing the SMR of male suicide and CCVD in 2007–2018 by period and four occupation groups, simila r to the recent linked data study [ 20 ]. As a result of sorting them into four occupational groups, the SMR of upper non-manual workers (MNG and PRF) was lower than that of other groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the 24-year period, SMR of suicide and CCVD were highest in SFF and MNG among males and females, respectively ( Appendix A ). Appendix B displays the result of analyzing the SMR of male suicide and CCVD in 2007–2018 by period and four occupation groups, simila r to the recent linked data study [ 20 ]. As a result of sorting them into four occupational groups, the SMR of upper non-manual workers (MNG and PRF) was lower than that of other groups.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the results of studies on occupational mortality in Korea are inconsistent. Some studies using unlinked data showed that male mortality of upper non-manual workers (MNG and PRF) turned out to be higher than that of manual workers in the mid-2010s, unlike in the late 1990s [ 9 , 19 ], whereas others reported that the mortality of manual workers remained the highest after the late 2000s [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations